Pulmonary hypertension and pregnancy outcomes: data from the Registry Of Pregnancy and Cardiac Disease (ROPAC) of the European Society of Cardiology. (7th July 2016) - Sliwa, Karen; van Hagen, Iris M.; Budts, Werner; Swan, Lorna; Sinagra, Gianfranco; Caruana, Maryanne; Blanco, Manuel Vazquez; Wagenaar, Lodewijk J.; Johnson, Mark R.; Webb, Gary; Hall, Roger; Roos‐Hesselink, Jolien W.; et al.
Abstract: Aims: To describe the outcomes of pregnancy in women with pulmonary hypertension. Methods and results: In 2007 the European Registry on Pregnancy and Heart Disease was initiated by the European Society of Cardiology. Consecutive patients with all forms of cardiovascular disease, presenting with pregnancy, were enrolled with the aim of investigating the pregnancy outcomes. This subgroup of the cohort included 151 women with pulmonary hypertension (PH) either diagnosed by right heart catheterization or diagnosed as possible PH by echocardiographic signs, with 26% having pulmonary arterial hypertension (PAH), in three subgroups: idiopathic (iPAH), associated with congenital heart disease (CHD‐PAH), or associated with other disease (oPAH), and 74% having PH caused by left heart disease (LHD‐PH, n  = 112). Maternal mean age was 29.2 ± 5.6 years and 37% were nulliparous. Right ventricular systolic pressure was <50 mmHg in 59.6% of patients, 50–70 mmHg in 28.5% and >70 mmHg in 11.9%. In more than 75% of patients, the diagnosis of PH had been made before pregnancy. Maternal death up to 1 week after delivery occurred in five patients (3.3%), with another two out of 78 patients who presented for follow‐up (2.6%), dying within 6 months after delivery. The highest mortality was found in iPAH (3/7, 43%). During pregnancy, heart failure occurred in 27%. Caesarean section was performed in 63.4% (23.9% as emergency). Therapeutic abortion was performed in 4.0%. Complications included miscarriage (5.6%), fetal mortality (2%), premature delivery (21.7%), low birth weight (19.0%), and neonatal mortality (0.7%). Conclusion: Mortality in this group of patients with various forms of PH was lower than previously reported as specialized care during pregnancy and delivery was available. However, maternal and fetal mortality remains prohibitively high in women with iPAH, although this conclusion is restricted by limited numbers. Early advice on contraception, pregnancy risk and fetal outcome remains paramount.